The Unified Supplementary Damping Method Based on Voltage-Soured Converter High-Voltage Direct Current Transmission Through Robust Control - Jinlei, Zhu; Yao, Zhang; Feixiang, Wu; Jiachang, Yi; Jiaqi, Wu (Frontiers in Energy Research, 2022)
The VSC-HVDC system can damp the inter-area low-frequency oscillation effectively. To enhance the ability of the VSC-HVDC supplementary control, this article proposes a unified low-frequency oscillation controller design using the robustness theory. The unified control strategy uses both the active power control and reactive power control loop of the VSC to expand the supplementary control dimensions. To design the controller, the TLS-ESPRIT identification method is used to obtain the system small signal model and the oscillation characteristic. Based on the model identified out, the linear matrix inequality method based robust control theory is applied for the controller design, and the robust controllers for active power control and reactive power control loop are both designed to improve the control effect. Finally, the simulation results show that the controller can reach better control effect and the robustness can also be guaranteed.